Índice de produtividade total dos fatores da agroindústria do estado de Minas Gerais - Santos, Márcio Henrique Teixeira (2008)
The present work aims to estimate the total productivity index of factors of production (FT) of agribusiness of Minas Gerais in the period from 1996 to 2005, covering 17 segments joined in 8 agribussiness sectors of Minas Gerais. The methodology is translog function trough the index of Tornqvist for measuring the overall productivity index. By using this technique, one intends to verify the behaviour of the indices of capital, labor, input, productivity and product for agribusiness sectors of Minas Gerais. Perfoming the calculations using the methodology of the index of Tornqvist in first moment, it was used the analysis data of the indices of total productivity through of data the Annua! Industrial Research.(IBGE). The results show that the indices of total productivity of the factors of the agribusiness are related variables investments, technologies and other. The indices of productivity found in the research show that the agribusiness of Minas Gerais had its rate of increase in productivity over the period analyzed. The agribusiness and industry of Minas Gerais have increased trajectory in most periods of analysis. The perfomance of productivity is due main1y by the volume of capital invested in the sector. The annua! growth rates of the indices of productivity of factors of agribusiness of Minas Gerais has increased from 0,68% for the productivity index, reduction of the input indices and product around 1.16% and 0.19%, and annua! growth indices of labour and capital around 1.17% and 4.05% in the analyzed period. It was concluded that policies for industrial development shoud be implemented after detailed studies of each sector of agribusiness of Minas Gerais, as each industrial section has its own chatacteristcs. These policies serve for agribusiness increasingly this type of conduct can lead to results that stuck or reduce the total productivity index, resulting drop in the levei of income, employment and production of Minas Gerais.